Ácido úrico e sua associação com o dano tubular e inflamação renal em pacientes com diabetes mellitus tipo 2 - Guarda, Naiara dos Santos (2017)
Hyperuricemia has emerged as a risk factor for the development of diabetes mellitus (DM) and consequently associated with the onset of diabetes kidney disease (DKD). It is known that the development of DKD is a complex process that promotes changes in different portions of the kidneys, and although hyperglycemia is a key mechanism in this process, it is not the only one. The inflammation has been evidenced as an important contributor to the pathophysiology of DKD. It is known that uric acid is a molecule that favors inflammation, both at the systemic and renal levels, contributing to kidney damage. In addition, uric acid has the potential to promote processes of afferent arteriolopathy, glomerular hypertrophy as well as direct damage to renal tubular cells. Damage to the renal tubules seems to be a primary contributor to the development of DKD and can be identified early by the presence of tubular damage markers. Despite the actions described, the mechanism by which uric acid acts in the context of DKD is not yet fully understood. Thus, the objective of this study was to evaluate the association between elevated uric acid levels and renal tubular damage, as well as its relation with renal inflammation in patients with type 2 diabetes mellitus (type 2 DM). A total of 125 patients with type 2 DM from the University Hospital of Santa Maria (HUSM), who had serum uric acid levels and other biochemical parameters measured, were recruited. In addition, urinary levels of the renal damage molecule-1 (KIM-1), used as a biomarker of tubular damage, and urinary levels of inflammatory cytokines such as interleukin-1 (IL-1), interleukin-6 ( IL- 6) and tumor necrosis factor alpha (TNF-alpha), used to check the renal inflammatory process. Patients were stratified into two groups according to the following levels of uric acid: <6.0 mg / dL and ≥6.0 mg / dL, and were compared for urinary levels of KIM-1, IL-1, IL -6 and TNF-alpha. Patients with higher serum uric acid levels were those who demonstrated higher urinary levels of KIM-1 and renal inflammation, as measured by quantification of urinary cytokines. It was also found that renal inflammation was positively correlated with the tubular damage process, as positive correlations were observed between the levels of KIM-1 and the proinflammatory cytokines evaluated in this study (IL-1, IL-6 and TNF-alpha ). Thus, we suggest that elevation of serum uric acid levels may be associated with a greater degree of tubular damage and renal inflammation in patients with type 2 DM. In addition, we believe that inflammation plays a significant role in the development of tubular renal damage and that uric acid may be promoting this inflammatory context.